Comparison of cardioprotective effects of mibefradil and ramipril in stroke-prone spontaneously hypertensive rats - XIA Qin-gui; REINECKE Alexander; DORENKAMP Marc; STORZ Christain; BITTERLING Havvo; PENZ Susanne; CLEUTJENS Jack; DAEMEN Mat JAP; SIMON Reichiger; UNGER Thomas (Acta Pharmacologica Sinica, 2016)
AIM: To elucidate the cardioprotective effects of T-type calcium channel blocker mibefradil and compare with that of the angiotensin-converting enzyme inhibitor ramipril in a stroke-prone spontaneously hypertensive rats (SHR-SP) model of congestive heart failure (CHF) after myocardial infarction (MI). METHODS: SHR-SP rats were subjected to permanent ligation of the left anterior decending coronary artery. Treatment with mibefradil (10 mg.kg(-1).d(-1)), ramipril (10 mg.kg(-1).d(-1)), or placebo was initiated 4 weeks before surgery and continued up to 6 weeks after induction of MI. Sham-operated rats served as controls. RESULTS: In placebo-treated MI rats, six weeks after MI, left ventricular circumference, inner diameter, and left ventricular end-diastolic pressure (LVEDP) were increased, whereas mean arterial blood pressure (MAP) and maximum rate of rise of left ventricular pressure (dp/dt(max)) were decreased compared with sham-operated controls (P